Strategi Pemerintah Desa Muara dalam Pengembangan Agrowisata - Aliyah Aliyah; Lina Aryani; Evi Priyanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
Tourism is often referred to as one of the keys to building a country's economy where currently many countries including Indonesia are trying to make the tourism sector one of the key sectors of economic development and help boost the country's foreign exchange. The Muara Village Government and Muara BUMDes made a tourism innovation, namely establishing a golden melon garden agrotourism. However, the potential of Golden Melon Agrotourism has not been fully developed to its full potential. There are several causes for the less than optimal development of agro-tourism, including the limited quality of human resources and the limited budget. The research was conducted to determine the strategy of the Muara village government in the development of agro-tourism. This research was conducted in Muara Village, Cilamaya Wetan District. Data was collected through observation, interviews and documentation. The data used in this study are primary data and secondary data. After obtaining the data, the researcher then analyzed the data, and the analytical methods used in this study were data reduction, data presentation and conclusion drawing. The results showed that the strategy carried out by the Muara Village government was still not optimal. This is seen through Kotten's theory where Kotten suggests that the types of strategies are divided into four, namely organizational strategy, program strategy, resource availability strategy and institutional strategy